Association of rheumatoid arthritis-related autoantibodies with pulmonary function test abnormalities in a rheumatoid arthritis registry - Huang, Sicong; He, Xintong; Doyle, Tracy J.; Zaccardelli, Alessandra; Marshall, Allison A.; Friedlander, H. Maura; Blaustein, Rachel B.; Smith, Elisabeth A.; Cui, Jing; Iannaccone, Christine K.; Mahmoud, Taysir G.; Weinblatt, Michael E.; et al. (Clinical rheumatology, 2019)
Introduction We investigated whether rheumatoid arthritis (RA)-related autoantibodies were associated with abnormalities on pulmonary function tests (PFTs). Methods We studied RA serostatus and PFT abnormalities within a RA registry. RA serostatus was assessed by research assays for cyclic citrullinated peptide (CCP) and rheumatoid factor (RF). Outcomes were abnormalities on clinically indicated PFTs, including restriction, obstruction, and diffusion abnormality. Logistic regression was used to obtain ORs and 95% CIs for the PFT abnormalities by RA serologic phenotypes independent of lifestyle and RA characteristics. Results Among 1272 analyzed subjects, mean age was 56.3 years (SD 14.1), 82.2% were female, and 69.5% were seropositive. There were 100 subjects with abnormal PFTs. Compared with seronegativity, seropositivity was associated with increased odds of any PFT abnormality (multivariable OR 2.29, 95% CI 1.30–4.03). When analyzing type of PFT abnormality, seropositivity was also associated with restriction, obstruction, and diffusion abnormalities; multivariable ORs were 2.48 (95% CI 1.26–4.87), 3.12 (95% CI 1.28–7.61), and 2.30 (95% CI 1.09–4.83), respectively. When analyzing by CCP and RF status, the associations were stronger for RF+ than for CCP+ (any PFT abnormality OR 1.99, 95% CI 1.21–3.27 for RF+ vs. RF−; OR 1.67, 95% CI 1.03–2.69 for CCP+ vs. CCP−) with a dose effect of higher RF titer increasing odds for each PFT abnormality ( p for trend < 0.05). Conclusions Seropositive RA patients had two-fold increased risk for abnormalities on PFTs performed for clinical indications compared with seronegative RA. Patients with seropositive RA, particularly those with high-titer RF positivity, may be more likely to have obstructive and restrictive abnormalities, independent of smoking. Key points • Due to the known excess pulmonary morbidity/mortality in RA, we studied the relationship of rheumatoid arthritis (RA)-related autoantibodies with pulmonary function test (PFT) abnormalities using a large RA registry. • We evaluated whether presence and levels of cyclic citrullinated peptide (CCP) and rheumatoid factor (RF) were associated with restriction, obstruction, and diffusion abnormalities on PFTs among 1272 subjects with RA. • Seropositivity was associated with two-fold increased risk for any PFT abnormality, independent of confounders including smoking. Higher titers of RF conferred greatest risk for all PFT outcomes: obstruction, restriction, and diffusion abnormality. • These results provide evidence that patients with RA should be closely monitored for pulmonary involvement, particularly those with high-titer RF seropositivity.